2021
DOI: 10.1080/12298093.2021.1940746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity and Population Structure Analysis among Germplasm of Agaricus bisporus by SSR Markers

Abstract: Agaricus bisporus is a popular edible mushroom that is cultivated worldwide. Due to its secondary homothallic nature, cultivated A. bisporus strains have low genetic diversity, and breeding novel strains is challenging. The aim of this study was to investigate the genetic diversity and population structure of globally collected A. bisporus strains using simple sequence repeat (SSR) markers. Agaricus bisporus strains were divided based on genetic distance-based groups and model-based subpopulations. The major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The whole-genome resequencing of 29 strains revealed that the Tibetan Plateau population was significantly differentiated from the European and American populations [ 33 ]. The commercial cultivars of A. bisporus have been studied used nuclear SSR and SNP markers, and the results showed they belonged to two groups [ 34 , 35 ]. However, the patterns of intraspecific evolution and population genetic history of A. bisporus remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The whole-genome resequencing of 29 strains revealed that the Tibetan Plateau population was significantly differentiated from the European and American populations [ 33 ]. The commercial cultivars of A. bisporus have been studied used nuclear SSR and SNP markers, and the results showed they belonged to two groups [ 34 , 35 ]. However, the patterns of intraspecific evolution and population genetic history of A. bisporus remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%